Peningkatan Kreativitas dan Pemahaman Siswa tentang Energi Terbarukan Melalui Perakitan Mobil Mainan Bertenaga Surya di SMP Baitul Hikmah - Ikhsan, Akhmad Fauzi; Nurpalah, Rifki; Nugroho, Ginaldi Ari; Sopian, Sani Moch; Wardani, Sekar Ayu Kusuma (Universitas Hamzanwadi, 2025)
This activity was organized with the aim of introducing the concept of renewable energy, particularly solar energy, to students of SMP Baitul Hikmah through the assembly of solar-powered toy cars. The program was designed to raise students' awareness of the importance of environmentally friendly energy while also enhancing their critical thinking skills and creativity in applying theory to practice. Throughout the activity, students actively participated in the assembly process and encountered various technical challenges that encouraged them to find solutions independently. As a result, the activity demonstrated an improvement in students' understanding of solar energy as well as the development of their creativity in completing assigned tasks.